Surgical outcome of infective endocarditis at Tygerberg Hospital from 2010-2019 : a retrospective review - Nel, Riaan Frederik (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.